Length–weight relationships of three fish species from Kerala waters, south‐west coast of India. (20th August 2017) - Roul, S. K.; Akhil, A. R.; Retheesh, T. B.; Prakasan, D.; Ganga, U.; Abdussamad, E. M.; Rohit, P.
Summary: Length–weight relationships (LWRs) of three fish species: Scomberomorus commerson, Alepes vari, and A. kleinii were estimated from Kerala waters, south‐west coast of India. Fish were captured between June 2016 and June 2017 by various gears such as ring seine (8–26 mm mesh size), trawl (30–40 mm cod end mesh size), hook and line (hook number VI–XII), smaller mesh sized drift gill net (26–90 mm) and larger one (120–170 mm) for bigger size fishes. Fish were collected on weekly basis from Cochin Fisheries Harbour (Lat. 09°56′327″N, Long. 76°15′764″E), Munambam Fisheries Harbour (Lat. 10°10′965″N, Long. 76°10′258″E), Kalamukku (Lat. 09°59′924″N, Long. 76°14′564″E) and Chellanam (Lat. 09°47′950″N, Long. 76°16′551″E). All LWRs were significant with r 2 values ranged from 0.944 to 0.996 and b values ranged from 2.722 to 3.021 ( p < .001). In addition, this study provides the information on LWRs and new maximum size for Alepes vari and A. kleinii .